A CNT cement-based self-sensing self-repairing material based on crack scale coupling and a preparation method and application thereof
Patent Information
- Application Number
- CN202611336093.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-30
AI Technical Summary
[0007]本发明的目的是克服现有自感知自修复复合水泥基材料中感知有效裂缝区间与修复有效裂缝区间尺度错位、功能协同性差,难以实现稳定联动的缺陷,从而提供一种基于裂缝尺度耦合的CNT水泥基自感知自修复材料及其制备方法和应用
[0046]本发明的制备方法可通过调控CNT掺量、分散状态及修复单元尺寸、壳体强度等参数,协同限定感知与修复的阈值区间,显著提升损伤响应的可预测性与工程可靠性;整体工艺基于成熟的CNT水泥基复合材料制备路线,通过裂缝尺度耦合设计实现自感知与自修复功能的协同,无需新增复杂工序即可实现由“性能增强型材料”向“损伤响应型智能材料”的功能升级,适配常规拌和、成型与养护流程,落地性强,具有良好的可实施性与推广潜力。
Smart Images

Figure CN123003223A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, and in particular to a CNT-based self-sensing and self-healing material based on crack scale coupling, its preparation method, and its application. Background Technology
[0002] Cement-based materials are currently the most widely used structural materials in civil engineering, extensively applied in various major infrastructure projects such as high-rise buildings, rail transit, underground tunnels, and water conservancy projects, undertaking core load-bearing and enclosure functions. Under the combined effects of long-term loads, alternating environmental temperature and humidity, erosion by harmful media, and the material's own shrinkage and creep, cracks of varying sizes inevitably develop within cement-based materials. The generation and propagation of cracks not only directly weaken the mechanical load-bearing capacity of the structure but also provide rapid intrusion channels for harmful media such as chloride ions, sulfates, and carbon dioxide, accelerating the deterioration of matrix hydration products and internal steel reinforcement corrosion, significantly reducing the structure's durability and service reliability, and substantially increasing the maintenance costs throughout the structure's life cycle. Therefore, how to achieve early and accurate detection and proactive repair of cracks in cement-based materials has become a core issue of key concern in the field of engineering materials.
[0003] In recent years, cement-based composites based on carbon nanotubes (CNTs) have been widely studied for self-sensing monitoring of structural cracks due to their conductive network properties. By introducing conductive functional phases such as CNTs, carbon fibers, and graphene into the cement matrix, combined with dispersion processes and interface modification methods, a stable conductive network can be formed within the matrix. When cracks or stress-strain occur within the material, the connectivity of the conductive pathways changes, leading to quantifiable changes in electrical parameters such as resistance and impedance, thereby achieving self-sensing monitoring of damage conditions. These materials do not require additional external sensors, have good compatibility with the cement matrix, and can achieve intelligent sensing of the structure itself. However, the functions of existing self-sensing cement-based materials are mostly limited to damage identification and condition monitoring. They can only characterize and provide early warnings of crack conditions, but cannot actively intervene in the generation and propagation of cracks. Damage will continue to develop, and the degradation of structural performance cannot be fundamentally inhibited.
[0004] On the other hand, self-healing cement-based materials, by introducing capsule-shaped or other forms of repair units, release repair substances after the crack has developed to a certain extent, thereby achieving crack closure or performance restoration. However, the triggering timing of existing self-healing systems is entirely determined by structural parameters such as the geometric dimensions of the repair unit itself, the mechanical strength of the shell, and the interfacial bonding characteristics. The crack width range in which they can effectively repair is relatively fixed, and they cannot be linked to the actual development state of the crack. Furthermore, they lack online sensing and quantitative evaluation methods for the repair triggering timing and repair effect, making it difficult to accurately grasp the repair process and repair quality in engineering applications.
[0005] To simultaneously possess crack detection and repair capabilities, existing technologies have incorporated conductive fillers and self-healing units into cement-based matrices, enabling materials to possess both detection and repair functions. However, these solutions are simply blending and superimposing of the two functional components, without establishing a synergistic matching mechanism between them at the material system design level. In actual service, there is often a significant dimensional mismatch between the crack width range where the conductive network can generate a stable and identifiable electrical response and the crack width range where the self-healing unit can be effectively triggered and perform its repair function. When the crack width is small, the conductive network can output a stable detection signal, but the local stress generated by the crack is insufficient to cause the repair unit to rupture, and the repair function cannot be triggered, resulting in a functional disconnect where the crack can be detected but not repaired. When the crack width is large, the repair unit can be triggered to release the repair agent, but the conductive network has already suffered severe fractures or even near-open circuits due to crack propagation, resulting in unstable or completely ineffective detection signals. This makes it impossible to continuously monitor the repair process and quantitatively evaluate the repair effect through electrical parameters.
[0006] Therefore, there is still a lack of existing technologies for cement-based functional materials that can use crack width as a unified design variable to coordinate the effective range of crack perception and crack repair from the material system design level, so that the two can stably correspond within the same crack width range. Summary of the Invention
[0007] The purpose of this invention is to overcome the shortcomings of existing self-sensing and self-healing composite cement-based materials, such as the misalignment of the effective crack sensing range and the effective crack repair range, poor functional synergy, and difficulty in achieving stable linkage. Therefore, this invention provides a CNT-based self-sensing and self-healing material based on crack scale coupling, its preparation method, and its applications. This CNT-based self-sensing and self-healing material uses crack width as a unified control variable. Through the collaborative design of CNT conductive network parameters and self-healing unit structural parameters, the effective crack sensing window and the effective crack repair window form a non-zero intersection, thereby simultaneously achieving stable electrical response and effective sealing repair of cracks within the same crack width range. Its preparation method is based on existing mature CNT-based material processes, and functional upgrades can be achieved without changing the basic preparation route. Its application allows for real-time monitoring of crack status and triggering of repair through electrical indicators, achieving closed-loop control of "real-time monitoring - threshold determination - active repair - effect verification." It is suitable for engineering scenarios with high durability and intelligent requirements, such as super high-rise buildings, rail transit, and underground engineering.
[0008] To achieve the above objectives, in a first aspect, the present invention provides a CNT-based self-sensing and self-healing material based on crack scale coupling, wherein the CNT-based self-sensing and self-healing material comprises a cement matrix and conductive functional units and self-healing units dispersed in the cement matrix. The conductive functional unit is a conductive network formed by carbon nanotubes in the cement-based material, which is used to respond to the generation and propagation of cracks through changes in electrical parameters; The self-healing unit is used to release a repair agent under the action of cracks, so as to achieve crack filling and structural performance restoration; The self-sensing effective crack window W of the CNT cement-based self-sensing and self-healing material s The crack width range within which the conductive functional unit can generate a stable and identifiable electrical response under the action of the crack; The self-healing effective crack window W of the CNT cement-based self-sensing and self-healing material h The self-healing unit is a crack width range that can be triggered under the action of cracks to achieve crack filling, reaction, or structural restoration. The self-sensing effective crack window W s With self-healing effective crack window W h The intersection is ,and .
[0009] Preferably, the raw materials of the cement-based matrix include silicate cement, standard sand, mixing water, and chemical admixtures.
[0010] More preferably, the mass ratio of the silicate cement to the standard sand is 1:2 to 4, and more preferably 1:3.
[0011] More preferably, the water-cement ratio of the cement-based matrix is 0.4 to 0.5, and more preferably 0.45.
[0012] More preferably, the standard sand is ISO standard sand conforming to GB / T 17671, with a particle size of 0.08~2.00mm.
[0013] More preferably, the chemical admixture includes defoamer and dispersant, and the total amount of chemical admixture is 0.5-1% of the mass of silicate cement.
[0014] More preferably, the mass ratio of defoamer to dispersant in the chemical admixture is 1:8~12.
[0015] More preferably, the defoamer is selected from one or more of silicone defoamers, polyether-modified silicone defoamers, higher alcohol defoamers, and polyether defoamers; More preferably, the dispersant is selected from one or more of polyvinyl alcohol, polycarboxylic acid dispersants, sodium dodecylbenzenesulfonate, and hydroxypropyl methylcellulose.
[0016] Preferably, the carbon nanotubes are carboxylated multi-walled carbon nanotubes with an outer diameter of 10-30 nm, a length of 5-30 μm, a purity of ≥95%, a carboxyl mass fraction of 1-3%, and a carbon nanotube content of 0.1-0.2% of the mass of silicate cement.
[0017] Preferably, the self-healing unit is selected from one or more of capsule-type repair units, fiber-type repair units, and microtubule-type repair units.
[0018] More preferably, the self-healing unit is a capsule-type self-healing unit, comprising a core containing repair material and a covering shell.
[0019] More preferably, the total dosage of the capsule-type repair unit is 0.5-10% of the mass of silicate cement, the average particle size is 50-500 μm, preferably 100-250 μm; the thickness of the coating shell is 0.5-5 μm, and the coating shell material is selected from one or more of urea-formaldehyde resin, melamine-formaldehyde, polyurea and polyurethane.
[0020] More preferably, the capsule-type repair unit is a two-component microcapsule system, including a first microcapsule and a second microcapsule, wherein the core of the first microcapsule is an epoxy resin and / or an epoxy prepolymer, and the core of the second microcapsule is a curing agent and / or a curing accelerator matched with the epoxy resin and / or epoxy prepolymer.
[0021] More preferably, the curing agent is selected from one or more of polyamide 650, diethylenetriamine, triethylenetetramine, and modified aliphatic amines.
[0022] More preferably, the curing accelerator is selected from one or more of 2,4,6-tris(dimethylaminomethyl)phenol, 2-ethyl-4-methylimidazolium, N,N-dimethylbenzylamine, and substituted urea.
[0023] More preferably, the mass ratio of the first microcapsule to the second microcapsule is 1:0.5~1, preferably 1:0.75.
[0024] More preferably, the capsule-type repair unit is a single-component latent microcapsule system, the core of which is a mixture of epoxy resin and / or epoxy prepolymer with latent curing agent and / or latent catalyst.
[0025] More preferably, the latent curing agent is selected from one or more of modified imidazole, dicyandiamide, organic hydrazide, and boron trifluoride-amine complex.
[0026] More preferably, the latent curing accelerator is selected from one or more of 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2,4,6-tris(dimethylaminomethyl)phenol and substituted urea.
[0027] More preferably, the mass ratio of the epoxy resin and / or epoxy prepolymer to the latent curing agent and / or latent catalyst is 1:0.10~0.20, preferably 1:0.15.
[0028] More preferably, the core of the capsule-shaped self-healing unit further includes a conductive filler, which is one or more of carbon nanotubes, carbon black, and graphene.
[0029] Preferably, the cement-based matrix further includes a polymer-modified phase, wherein the polymer-modified phase is carboxylated styrene-butadiene latex, and the solid content of the carboxylated styrene-butadiene latex is 48-52%.
[0030] More preferably, the amount of the polymer-modified phase, based on the dry polymer mass, accounts for 2 to 8% of the mass of silicate cement, preferably 5%.
[0031] Secondly, the present invention provides a method for preparing CNT cement-based self-sensing and self-healing materials as described herein, the method comprising the following steps: 1) Preparation of carbon nanotube aqueous dispersion: Add carbon nanotubes to part of the mixing water, add dispersant, mechanically stir at a stirring rate of 800~1200r / min for 3~8min, then ultrasonically disperse at a power density of 50~100W / L for 10~60min, let stand for 10min, and take the upper uniform dispersion as carbon nanotube aqueous dispersion. 2) Dry material premixing: Put silicate cement and standard sand into a mixer and dry mix at a mixing rate of 60~150r / min for 1~3min to obtain mixed dry material; 3) Slurry mixing: Add the carbon nanotube aqueous dispersion, polymer modified phase, defoamer and remaining mixing water mentioned in step 1) to the mixed dry material, stir at a stirring rate of 120~180 r / min for 2~4 min, and then stir at a stirring rate of 250~300 r / min for 2~4 min until the slurry is uniform. 4) Introduce self-healing units: Add self-healing units to the slurry that has been mixed evenly in step 3), stir at low speed to disperse the self-healing units evenly, and obtain a mixture; 5) Molding and curing: Pour the mixture obtained in step 4) into a mold and perform standard curing until the specified age is reached to obtain the CNT cement-based self-sensing and self-healing material.
[0032] Preferably, in step 1), the dispersant is selected from one or more of polyvinyl alcohol, polycarboxylic acid dispersants, sodium dodecylbenzenesulfonate, and hydroxypropyl methylcellulose.
[0033] Preferably, in step 1), the mass ratio of the carbon nanotubes, dispersant, and part of the mixing water is 1:(2.5~5):(100~200).
[0034] Preferably, in step 5), the standard curing conditions include: an ambient temperature of 18~22℃, a relative humidity of ≥95%, and a curing age of ≥28 days; after pouring, the formwork is removed after standing for 20~24 hours, and then the formwork is placed in the standard curing environment for curing until the specified age.
[0035] Preferably, the preparation method further includes pre-embedding electrodes during the molding process of the CNT cement-based self-sensing and self-healing material; the electrodes are used to apply voltage or current to the CNT cement-based self-sensing and self-healing material to generate Joule heating in the conductive network.
[0036] Thirdly, the present invention provides an application of the CNT cement-based self-sensing and self-healing material as described in the present invention in the health monitoring and crack self-repair of structures in super high-rise buildings, rail transit or underground engineering.
[0037] Fourthly, the present invention provides a method for the coordinated operation of crack self-sensing and self-repairing using the CNT cement-based self-sensing and self-repairing material described in the present invention, the method comprising the following steps: S1. Initial state and real-time monitoring: CNT cement-based self-sensing and self-healing materials in good service condition conduct real-time electrical monitoring through internal conductive functional units, continuously collect electrical index S, and dynamically sense the generation and expansion state of cracks. S2. Damage signal discrimination: When the real-time acquired electrical index S enters the electrical threshold window When, and the signal duration is ≥ t n If the condition is not met, proceed to the coupling window determination stage; if the determination condition is not met, return to step S1 to maintain the real-time monitoring state. S3. Entering Critical State and Repair Trigger: Determine whether the crack width W corresponding to the current electrical index S falls within the crack scale coupling window. Confirm entry into the crack-scale coupling window. Then, the corresponding repair mechanism is triggered: When a two-component microcapsule self-healing unit is used, a passive triggering mode is adopted, which relies on the stress of crack propagation to rupture the microcapsule shell, and the two-component repair agent is released into the crack space simultaneously. When using a single-component latent microcapsule self-healing unit, an active triggering mode is adopted. By applying voltage or current to the built-in electrodes of the CNT cement-based self-sensing self-healing material, the Joule heating effect of the conductive functional unit is used to raise the temperature of the crack area to a preset temperature range, thereby activating the latent curing component to start and accelerate the repair reaction. S4. Crack filling and conductive network reconstruction: The repair agent flows into the crack space and solidifies, filling the crack defects and bridging the crack interface; at the same time, the conductive path in the repaired area is gradually reconstructed, and the electrical index S of the CNT cement-based self-sensing self-healing material gradually decreases with the repair process. S5. Closed-loop verification of repair effect: After the repair is completed, obtain the electrical index S after repair. a And calculate the electrical recovery rate η R ; If the electrical index S is repaired a ≤Damage threshold Ω, and electrical recovery rate η R If the value is ≥0.75, the repair is considered successful. The CNT cement-based self-sensing and self-healing material is restored to a state where it can continue to be used. Return to step S1 to enter the next monitoring cycle. If the electrical index Sa after repair is greater than the damage assessment threshold Ω, or the electrical recovery rate η R If the value is less than 0.75, the repair is deemed insufficient, triggering a secondary repair process or issuing a damage alarm.
[0038] Preferably, in step S1, the electrical index S is the relative resistance change rate ΔR / R or the impedance change.
[0039] Preferably, the electrical response of the CNT cement-based self-sensing and self-healing material is tested in advance under different crack widths to establish the correspondence between the electrical index S and the crack width W, and to determine the coupling window with crack scale. Corresponding electrical threshold window Simultaneously, a damage assessment threshold Ω and a minimum duration assessment time t are set. n .
[0040] Preferably, when the electrical index S is the relative resistance change rate ΔR / R, Ω is 5%; when the electrical index S is the impedance change, Ω is the impedance change corresponding to the smallest identifiable crack.
[0041] Preferably, in step S2, the shortest duration determination time t n The duration is 10~60 seconds.
[0042] Preferably, in step S5, the electrical recovery rate η R Satisfying η R =(R p -R a ) / (R p- R0), where R0 is the initial resistance, R p R is the peak resistance at the crack. a The resistor after repair.
[0043] Preferably, if η R =1 indicates that the resistance has completely returned to its initial state, if ηR =0 indicates that the resistance did not decrease at all after the repair, and there was no repair effect whatsoever; if 1≥η R A value ≥0.75 indicates a good repair effect; if 0 < η R A value <0.75 indicates insufficient repair effect.
[0044] Preferably, in step S5, the repaired electrical index S a This refers to the rate of change of relative resistance or the amount of change of impedance after repair.
[0045] In the above technical solution, the CNT cement-based self-sensing and self-healing material of the present invention introduces the concept of crack scale coupling design, using crack width W as a unified control variable to construct self-sensing effective crack windows W respectively. s With self-healing effective crack window W h And regulate the two to form a stable non-zero intersection. This approach addresses the fundamental shortcomings of existing composite systems, such as misalignment of effective sensing and repair ranges and poor functional synergy. It ensures that the crack width W can simultaneously achieve stable electrical sensing and effective autonomous repair within the coupling range, avoiding functional disconnects such as "cracks are detectable but repair units are not triggered" or "cracks have repair conditions but the sensing signal is unstable." Furthermore, the microcrack bridging effect of CNTs, combined with the optimized interface effect of polymer modification, can suppress crack propagation and improve matrix toughness and damping characteristics while achieving intelligent functions, balancing basic mechanical properties and crack control capabilities. After repair, the cross-crack conductive pathway can be effectively reconstructed. Combined with the self-healing units dispersed in the matrix, it can achieve multiple damage responses to cracks in multiple locations and batches, ensuring the continuous effectiveness of the function.
[0046] The preparation method of this invention can significantly improve the predictability and engineering reliability of damage response by controlling parameters such as CNT dosage, dispersion state, repair unit size, and shell strength, and synergistically limiting the threshold range of sensing and repair. The overall process is based on a mature CNT cement-based composite material preparation route. Through crack-scale coupling design, it achieves synergy between self-sensing and self-repairing functions. It can realize the functional upgrade from "performance-enhanced material" to "damage-responsive smart material" without adding complex processes. It is compatible with conventional mixing, molding, and curing processes, has strong applicability, and has good feasibility and promotion potential.
[0047] Meanwhile, the CNT cement-based self-sensing and self-healing material system of the present invention has a wide range of adjustable parameters, and the position and width of the coupling window can be flexibly designed to adapt to the crack control requirements of different service scenarios.
[0048] Furthermore, this invention obtains a correlation between the electrical index S and the crack width W by pre-establishing the relationship between them. Corresponding electrical threshold window When the real-time monitored S enters The system can immediately determine if a crack has entered the coupling window and trigger a repair strategy, forming a closed-loop control logic of "real-time monitoring - threshold determination - active repair - effect verification". Because the self-healing units are dispersed within the matrix, CNT cement-based self-sensing self-healing materials can trigger and repair multiple cracks occurring at different locations and times during service. For repeated repairs of the same crack, a continuous supply repair structure can be further employed to achieve a higher number of repair cycles. The electrical recovery rate η is monitored in real time. R It can effectively assess the repair effect and guide subsequent maintenance decisions. It is suitable for cement-based engineering materials fields with high requirements for durability, functionality and intelligence, such as super high-rise buildings, rail transit, and underground engineering.
[0049] Other features and advantages of the present invention will be described in detail in the following detailed description section. Attached Figure Description
[0050] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the following detailed description to explain the invention, but do not constitute a limitation thereof. In the drawings: Figure 1 This is a schematic diagram of the structure of the CNT cement-based self-sensing and self-healing material of the present invention; Figure 2 This is a schematic diagram of the crack change sensing mechanism of the present invention; Figure 3 This is a schematic diagram of the self-healing process of the present invention; Figure 4 This is a schematic diagram of crack scale coupling in the present invention; Figure 5 This is a schematic diagram of the self-sensing and self-repairing process of the present invention.
[0051] Figure Labels 1-Cement-based substrate; 2-CNT conductive network; 3-Self-healing unit; 4-Repair agent; 5-Crack; 6-Electrode; 7-Signal acquisition and processing module; 8-Judgment and control module. Detailed Implementation
[0052] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0053] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0054] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0055] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0056] In a first aspect, the present invention provides a CNT-based self-sensing and self-healing material based on crack scale coupling, wherein the CNT-based self-sensing and self-healing material comprises a cement matrix and conductive functional units and self-healing units dispersed in the cement matrix. The conductive functional unit is a conductive network formed by carbon nanotubes in the cement-based material, which is used to respond to the generation and propagation of cracks through changes in electrical parameters; The self-healing unit is used to release a repair agent under the action of cracks, so as to achieve crack filling and structural performance restoration.
[0057] This invention defines the self-sensing effective crack window W of the CNT cement-based self-sensing and self-healing material. s The crack width range within which the conductive functional unit can generate a stable and identifiable electrical response under the action of a crack.
[0058] This invention defines the effective crack window W for self-healing of the CNT cement-based self-sensing and self-healing material. h The self-healing unit is a crack width range that can be triggered under the action of cracks to achieve crack filling, reaction, or structural restoration.
[0059] Through the coordinated regulation of the parameters of the CNT cement-based self-sensing and self-healing material, the effective crack window W of the self-sensing material is made more efficient. sWith self-healing effective crack window W h The intersection is ,and That is, the self-perceived effective crack window W. s With self-healing effective crack window W h intersection Not an empty set. When the crack width W falls into Within the specified range, the CNT cement-based self-sensing and self-healing material can simultaneously achieve stable electrical identification and autonomous repair of cracks, ensuring coordinated matching of sensing and repair actions.
[0060] The CNT cement-based self-sensing and self-healing material of this invention introduces the concept of crack scale coupling design, using crack width W as a unified control variable to construct self-sensing effective crack windows W. s With self-healing effective crack window W h And regulate the two to form a stable non-zero intersection. This approach addresses the fundamental shortcomings of existing composite systems, such as misalignment of effective sensing and repair ranges and poor functional synergy. It ensures that the crack width W can simultaneously achieve stable electrical sensing and effective autonomous repair within the coupling range, avoiding functional disconnects such as "cracks are detectable but repair units are not triggered" or "cracks have repair conditions but the sensing signal is unstable." Furthermore, the microcrack bridging effect of CNTs, combined with the optimized interface effect of polymer modification, can suppress crack propagation and improve matrix toughness and damping characteristics while achieving intelligent functions, balancing basic mechanical properties and crack control capabilities. After repair, the cross-crack conductive pathway can be effectively reconstructed. Combined with the self-healing units dispersed in the matrix, it can achieve multiple damage responses to cracks in multiple locations and batches, ensuring the continuous effectiveness of the function.
[0061] In this invention, the raw materials of the cement-based matrix include silicate cement, standard sand, mixing water, and chemical admixtures. Silicate cement is selected as the cementitious material because its hydration products are stable and have good compatibility with carbon nanotubes and microcapsules, serving as the basic load-bearing phase of the CNT cement-based self-sensing and self-healing material.
[0062] Standard sand, as aggregate, forms the skeleton component of the CNT cement-based self-sensing and self-healing material, and its dosage directly affects the material's mechanical strength and volume stability. In this invention, the mass ratio of silicate cement to standard sand is 1:2 to 4, preferably 1:3. Within this ratio range, the material can be guaranteed to possess both good mechanical properties and volume stability.
[0063] In this invention, the water-cement ratio of the cement-based matrix is 0.4~0.5, preferably 0.45.
[0064] In this invention, the chemical admixtures include defoamers and dispersants, and the total amount of chemical admixtures is 0.5-1% of the mass of silicate cement.
[0065] In this invention, the mass ratio of defoamer to dispersant in the chemical additive is 1:8~12.
[0066] In this invention, the defoamer is selected from one or more of silicone defoamers, polyether-modified silicone defoamers, higher alcohol defoamers, and polyether defoamers; In this invention, the dispersant is selected from one or more of polyvinyl alcohol, polycarboxylic acid dispersants, sodium dodecylbenzenesulfonate, and hydroxypropyl methylcellulose.
[0067] In this invention, the carbon nanotubes are carboxylated multi-walled carbon nanotubes with an outer diameter of 10-30 nm, a length of 5-30 μm, a purity ≥95%, a carboxyl group mass fraction of 1-3%, and a carbon nanotube dosage of 0.1-0.2% of the silicate cement mass. This dosage range is used to regulate the effective crack window W of the self-sensing system. s The core approach is that when the doping concentration is below 0.1%, carbon nanotubes cannot form a continuous conductive permeation network within the matrix. The material resistivity is too high, and the electrical response is weak when microcracks occur, making stable identification impossible, leading to W... s The lower limit is too high and the effective range is too narrow; when the doping concentration is higher than 0.2%, carbon nanotubes are prone to aggregation, which not only degrades the mechanical properties of the matrix but also reduces the sensitivity of the conductive network to crack width. s If the upper limit is too high and the response range is too wide, it is difficult to accurately match the self-healing window. By controlling the dosage within the above range, the effective crack window for self-sensing can be kept within a reasonable range, providing a basis for subsequent scale coupling.
[0068] In this invention, the self-repairing unit is selected from one or more of capsule-type repair units, fiber-type repair units, and microtubule-type repair units.
[0069] In a preferred embodiment of the present invention, the self-healing unit is a capsule-shaped self-healing unit, which has the advantages of mature preparation technology, simple addition process, controllable trigger threshold, and good compatibility with cement-based matrix, making it the optimal carrier for realizing scale-coupled design. The capsule-shaped self-healing unit includes a core containing repair material and a covering shell, and its core structural parameters directly determine the effective crack window W for self-healing. h The range.
[0070] In this invention, the total dosage of the capsule-shaped repair unit is 0.5-10% of the mass of silicate cement, which can be flexibly adjusted according to the target repair efficiency; if the dosage is too low, the total amount of repair agent will be insufficient, and wide cracks cannot be completely filled. h The upper limit is too low; if the dosage is too high, too many weak phases will be introduced, which will significantly reduce the mechanical strength of the matrix.
[0071] In this invention, the average particle size of the capsule-shaped repair unit is 50~500μm, preferably 100~250μm; the thickness of the encapsulated shell is 0.5~5μm. The particle size and shell thickness together determine the triggering threshold of the repair unit (i.e., the minimum crack width required to tear the shell): when the particle size is too small and the shell is too thick, the required crack width for triggering is large. h If the lower limit is too high, a mismatch may occur where "cracks are detectable but repair is not triggered." If the particle size is too large or the shell is too thin, the shell is prone to premature failure and ineffectiveness during mixing, and the trigger threshold is too low, causing the repair agent to be released too early and unable to match the crack propagation process. By adjusting the particle size and shell thickness, W can be precisely adjusted. h The upper and lower limit positions are used to achieve the same effect as W. s Matching coupling.
[0072] The encapsulation shell material of the capsule-shaped repair unit is selected from one or more of urea-formaldehyde resin, melamine-formaldehyde, polyurea, and polyurethane.
[0073] For different application scenarios, capsule-type repair units can adopt a two-component passive system or a single-component latent active system: (1) The capsule-type repair unit is a two-component microcapsule system, including a first microcapsule and a second microcapsule. The core of the first microcapsule is epoxy resin and / or epoxy prepolymer, and the core of the second microcapsule is a curing agent and / or curing accelerator that matches the epoxy resin and / or epoxy prepolymer.
[0074] In this invention, the curing agent is selected from one or more of polyamide 650, diethylenetriamine, triethylenetetramine, and modified aliphatic amines.
[0075] In this invention, the curing accelerator is selected from one or more of 2,4,6-tris(dimethylaminomethyl)phenol, 2-ethyl-4-methylimidazole, N,N-dimethylbenzylamine, and substituted urea.
[0076] In this invention, the mass ratio of the first microcapsule to the second microcapsule is 1:0.5~1, preferably 1:0.75.
[0077] (2) The capsule-type repair unit is a single-component latent microcapsule system, the core of which is a mixture of epoxy resin and / or epoxy prepolymer with latent curing agent and / or latent catalyst.
[0078] In this invention, the latent curing agent is selected from one or more of modified imidazole, dicyandiamide, organic hydrazide, and boron trifluoride-amine complex.
[0079] In this invention, the latent curing accelerator is selected from one or more of 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2,4,6-tris(dimethylaminomethyl)phenol and substituted urea.
[0080] In this invention, the mass ratio of the epoxy resin and / or epoxy prepolymer to the latent curing agent and / or latent catalyst is 1:0.10~0.20, preferably 1:0.15.
[0081] In this invention, the core of the capsule-shaped self-healing unit further includes a conductive filler, which is one or more of carbon nanotubes, carbon black, and graphene. The epoxy resin in the self-healing unit, after curing, is an insulating phase; after crack repair, it blocks the original conductive network, causing the material's sensing function to fail. By introducing the conductive filler into the core, the repair agent can form a cross-crack conductive bridge at the crack during curing, significantly improving the electrical recovery rate after repair and ensuring that the material retains continuous crack sensing capability after repair, providing a functional basis for multiple damage-repair cycles.
[0082] In this invention, the cement-based matrix further includes a polymer-modified phase, which is a carboxylated styrene-butadiene latex with a solid content of 48-52%. This phase improves the dispersion stability of carbon nanotubes by further inhibiting their aggregation through the steric hindrance of the polymer chains, thus optimizing the uniformity of the conductive network. Furthermore, it improves the interfacial toughness of the cement-based matrix, gradually releasing the interfacial stress concentration between the capsule-type self-healing unit and the matrix, while simultaneously enhancing the response stability of the conductive network during crack propagation.
[0083] In this invention, the amount of the polymer-modified phase, based on the dry polymer mass, accounts for 2 to 8% of the mass of silicate cement, preferably 5%.
[0084] Secondly, the present invention provides a method for preparing CNT cement-based self-sensing and self-healing materials as described herein, the method comprising the following steps: 1) Preparation of carbon nanotube aqueous dispersion: Add carbon nanotubes to part of the mixing water, add dispersant, mechanically stir at a stirring rate of 800~1200r / min for 3~8min, then ultrasonically disperse at a power density of 50~100W / L for 10~60min, let stand for 10min, and take the upper uniform dispersion as carbon nanotube aqueous dispersion. 2) Dry material premixing: Put silicate cement and standard sand into a mixer and dry mix at a mixing rate of 60~150r / min for 1~3min to obtain mixed dry material; 3) Slurry mixing: Add the carbon nanotube aqueous dispersion, polymer modified phase, defoamer and remaining mixing water mentioned in step 1) to the mixed dry material, stir at a stirring rate of 120~180 r / min for 2~4 min, and then stir at a stirring rate of 250~300 r / min for 2~4 min until the slurry is uniform. 4) Introduce self-healing units: Add self-healing units to the slurry that has been mixed evenly in step 3), stir at low speed to disperse the self-healing units evenly, and obtain a mixture; 5) Molding and curing: Pour the mixture obtained in step 4) into a mold and perform standard curing until the specified age is reached to obtain the CNT cement-based self-sensing and self-healing material.
[0085] The preparation method of this invention can significantly improve the predictability and engineering reliability of damage response by controlling parameters such as CNT dosage, dispersion state, repair unit size, and shell strength, and synergistically limiting the threshold range of sensing and repair. The overall process is based on a mature CNT cement-based composite material preparation route. Through crack-scale coupling design, it achieves synergy between self-sensing and self-repairing functions. It can realize the functional upgrade from "performance-enhanced material" to "damage-responsive smart material" without adding complex processes. It is compatible with conventional mixing, molding, and curing processes, has strong applicability, and has good feasibility and promotion potential.
[0086] In step 1) of this invention, the dispersant is selected from one or more of polyvinyl alcohol, polycarboxylic acid dispersants, sodium dodecylbenzenesulfonate, and hydroxypropyl methylcellulose.
[0087] In step 1) of this invention, the mass ratio of the carbon nanotubes, dispersant and part of the mixing water is 1:(2.5~5):(100~200).
[0088] In step 5) of this invention, the standard curing conditions include: an ambient temperature of 18~22℃, a relative humidity of ≥95%, and a curing age of ≥28 days; after pouring, the mold is removed after standing for 20~24 hours, and then the mold is placed in the standard curing environment for curing until the specified age.
[0089] In this invention, the preparation method further includes pre-embedding electrodes during the molding process of the CNT cement-based self-sensing and self-healing material. The electrodes are typically copper sheet or stainless steel mesh electrodes, pre-embedded in a designated monitoring section of the component. The electrodes have two main functions: first, they can be connected to external testing equipment to collect the resistance / impedance signal of the material in real time, realizing self-sensing of cracks; second, in a single-component latent system, they are used to apply working voltage or current to the conductive network, utilizing the Joule heating effect of carbon nanotubes to raise the temperature of the crack area, activate the latent curing agent, and achieve active repair triggering.
[0090] Thirdly, the present invention provides an application of the CNT cement-based self-sensing and self-healing material as described in the present invention in the health monitoring and crack self-repair of structures in super high-rise buildings, rail transit or underground engineering.
[0091] The aforementioned engineering scenarios are generally characterized by complex service environments, high structural maintenance difficulty, and high maintenance costs: cracks in the vertical components of super high-rise buildings can affect structural safety and durability; rail transit structures are subjected to long-term dynamic loads, making micro-cracks prone to propagation; underground engineering projects are subject to erosion by groundwater and corrosive media, and cracks accelerate structural deterioration. The material of this invention integrates load-bearing, self-sensing, and self-repairing functions, enabling early identification and autonomous repair of crack damage without relying on external sensors or manual maintenance. This significantly improves structural service safety, reduces life-cycle maintenance costs, and demonstrates significant engineering value and economic benefits.
[0092] like Figure 5 As shown, in a fourth aspect, the present invention provides a method for the coordinated operation of crack self-sensing and self-repairing using the CNT cement-based self-sensing and self-repairing material described in the present invention, the method comprising the following steps: S1. Initial state and real-time monitoring: The CNT cement-based self-sensing and self-healing material in good service condition conducts real-time electrical monitoring through its internal conductive functional unit, continuously collects electrical index S, and dynamically senses the generation and expansion state of cracks. S2. Damage signal discrimination: When the real-time acquired electrical index S enters the electrical threshold window When, and the signal duration is ≥ t n If the condition is not met, proceed to the coupling window determination stage; if the determination condition is not met, return to step S1 to maintain the real-time monitoring state. S3. Entering Critical State and Repair Trigger: Determine whether the crack width W corresponding to the current electrical index S falls within the crack scale coupling window. Confirm entry into the crack-scale coupling window. Then, the corresponding repair mechanism is triggered: When a two-component microcapsule self-healing unit is used, a passive triggering mode is adopted, which relies on the stress of crack propagation to rupture the microcapsule shell, and the two-component repair agent is released into the crack space simultaneously. When using a single-component latent microcapsule self-healing unit, an active triggering mode is adopted. By applying voltage or current to the built-in electrodes of the CNT cement-based self-sensing self-healing material, the Joule heating effect of the conductive functional unit is used to raise the temperature of the crack area to a preset temperature range, thereby activating the latent curing component to start and accelerate the repair reaction. S4. Crack filling and conductive network reconstruction: The repair agent flows into the crack space and solidifies, filling the crack defects and bridging the crack interface; at the same time, the conductive path in the repaired area is gradually reconstructed, and the electrical index S of the CNT cement-based self-sensing self-healing material gradually decreases with the repair process. S5. Closed-loop verification of repair effect: After the repair is completed, obtain the electrical index S after repair. a And calculate the electrical recovery rate η R ; If the electrical index S is repaired a ≤Damage threshold Ω, and electrical recovery rate η R If the value is ≥0.75, the repair is considered successful. The CNT cement-based self-sensing and self-healing material is restored to a state where it can continue to be used. Return to step S1 to enter the next monitoring cycle. If the electrical index Sa after repair is greater than the damage assessment threshold Ω, or the electrical recovery rate η R If the value is less than 0.75, the repair is deemed insufficient, triggering a secondary repair process or issuing a damage alarm, prompting manual intervention for investigation.
[0093] In this invention, in step S1, the electrical index S is the relative resistance change rate ΔR / R or the impedance change.
[0094] In this invention, the electrical response of the CNT cement-based self-sensing and self-healing material under different crack widths is tested in advance to establish the correspondence between the electrical index S and the crack width W, and to determine the coupling window with crack scale. Corresponding electrical threshold window Simultaneously, a damage assessment threshold Ω and a minimum duration assessment time t are set. n .
[0095] In this invention, the damage determination threshold Ω is a critical value of electrical index used to determine whether there is still identifiable residual damage in the CNT cement-based self-sensing self-healing material after the repair is completed; the damage determination threshold Ω is pre-calibrated based on the baseline electrical response of the intact state and the electrical response corresponding to the smallest identifiable crack.
[0096] When the electrical index S is the relative resistance change rate ΔR / R, Ω is 5%; when the electrical index S is the impedance change, Ω is determined based on the baseline fluctuation range of the intact state of the same material system and the impedance change corresponding to the smallest identifiable crack.
[0097] In step S2 of this invention, the shortest duration determination time t n The duration is set to 10~60s. The core function of this duration setting is to eliminate instantaneous changes in resistance signals caused by factors such as instantaneous load fluctuations and electromagnetic interference, thereby avoiding false triggering of repair actions and improving the reliability of damage identification.
[0098] In step S5 of the present invention, the electrical recovery rate η R Satisfying η R =(R p -R a ) / (R p- R0), where R0 is the initial resistance, R p R is the peak resistance at the crack. a The resistor after repair.
[0099] In this invention: If η R =1 indicates that the resistance has been completely restored to its initial state, and the conductive network reconstruction effect is optimal. If η R =0 indicates that the resistance did not decrease at all after the repair, and there was no repair effect whatsoever. If 1 ≥ η R A value ≥0.75 indicates a good repair effect, with both mechanical properties and sensory function effectively restored; If 0 < η R A value <0.75 indicates insufficient repair effect, requiring secondary repair or manual intervention.
[0100] In step S5 of this invention, the repaired electrical index S a This refers to the rate of change of relative resistance or the amount of change of impedance after repair.
[0101] It should be noted that the electrical recovery rate η R After repair, the resistor R a These parameters are calculated and can only be obtained after the repair is complete. They are used in step S5 to evaluate the recovery degree of the conductive network, but not in step S2 for damage trigger determination. Step S2 still uses whether the electrical index S enters the electrical threshold window. And the duration reaches t n As a criterion.
[0102] The present invention will be described in detail below through examples, but the scope of protection of the present invention is not limited thereto. In the following examples, the drugs and pharmaceuticals are all conventional commercially available products.
[0103] The sources and specifications of the raw materials used in the following examples and comparative examples are as follows: • Cement: Ordinary Portland cement (P·O42.5 grade); • Standard sand: ISO standard sand conforming to GB / T 17671, with a particle size of 0.08~2.00mm; • Polymer-modified phase: Carboxylated styrene-butadiene latex (SBR), with a solid content of 50±2%; • Dispersant: Polyvinyl alcohol (PVA), with a degree of alcoholysis of 87-89 mol% • Defoamer: Silicone defoamer, with an effective ingredient content ≥30%; • Mixing water: Deionized water, water for dispersing carbon nanotubes and water contained in carboxylated styrene-butadiene latex are all included in the total amount of mixing water; • Conductive functional unit: Carboxylated multi-walled carbon nanotubes with an outer diameter of 10~30nm, a length of 5~30μm, a purity of ≥95%, and a carboxyl mass fraction of 1~3%; • Self-healing unit: Utilizes custom-designed polyurethane shell microcapsules with an average particle size of 150±30μm and a shell thickness of 2±0.5μm. a. Two-component capsule system: Two-component microcapsule type A (epoxy resin microcapsule): The core is E-51 epoxy resin containing conductive carbon black, the amount of conductive carbon black is 1% of the mass of E-51 epoxy resin, the average particle size is 150±30μm, the shell thickness is 2±0.5μm, and the shell material is polyurethane. Two-component microcapsules, type B (curing agent microcapsules): The core is a mixture of polyamide 650 and 2,4,6-tris(dimethylaminomethyl)phenol in a mass ratio of 100:3, with an average particle size of 150±30μm and a shell thickness of 2±0.5μm. The shell material is polyurethane. b. Single-component microcapsules: The core is a homogeneous mixture of E-51 epoxy resin, modified imidazole latent curing agent and conductive carbon black. The mass ratio of E-51 epoxy resin to modified imidazole latent curing agent is 100:15. The amount of conductive carbon black is 1% of the mass of E-51 epoxy resin. The average particle size is 150±30μm, the shell thickness is 2±0.5μm, and the shell material is polyurethane.
[0104] Example 1 1. Mixing ratio: This embodiment provides a CNT cement-based self-sensing and self-healing material based on crack scale coupling, which adopts a two-component microcapsule system, and its formulation is shown in Table 1 (based on 100 parts by cement mass).
[0105]
[0106] 2. Preparation steps: (1) Preparation of carbon nanotube dispersion: Carbon nanotubes and polyvinyl alcohol dispersant were added to 20 parts of deionized water according to the ratio. The mixture was first mechanically stirred for 5 min at a stirring rate of 800 r / min to initially wet and disperse it. Then, it was ultrasonically dispersed for 30 min at a power density of 80 W / L. After standing for 10 min, the upper uniform dispersion was taken for use.
[0107] (2) Dry mixing: Put ordinary silicate cement and standard sand into a mortar mixer and dry mix for 3 minutes at a mixing rate of 140±5r / min until the mixture is uniform.
[0108] (3) Slurry mixing: Add carbon nanotube dispersion, carboxylated styrene-butadiene latex, silicone defoamer and remaining mixing water to the dry material in step (2). First, stir at a stirring rate of 140±5r / min for 2min, and then stir at a stirring rate of 285±10r / min for 3min until the slurry is homogeneous.
[0109] (4) Microcapsule introduction: Add two-component type A microcapsules and type B microcapsules to the slurry in step (3) and stir at a stirring rate of 80 r / min for 2 min to make the microcapsules uniformly dispersed and keep the shell intact.
[0110] (5) Molding and curing: The slurry containing microcapsules in step (4) is poured into a 40mm×40mm×160mm prism mold, vibrated and compacted on a vibrating table, and the surface is smoothed and placed in a standard curing room (temperature 20±2℃, relative humidity ≥95%) for curing. After 24 hours, the mold is removed and curing continues until 28 days of age to obtain CNT cement-based self-sensing and self-healing material, which is denoted as B1.
[0111] Example 2 1. Mixing ratio The difference between this embodiment and Embodiment 1 is that the self-healing unit is a single-component latent microcapsule system, while the rest of the composition is the same as in Embodiment 1. The formulation is shown in Table 2.
[0112]
[0113] 2. Preparation steps: (1) Preparation of carbon nanotube dispersion: Same as in Example 1.
[0114] (2) Dry material mixing: Same as in Example 1.
[0115] (3) Slurry mixing: Same as in Example 1.
[0116] (4) Microcapsule introduction: Add single-component microcapsules to the slurry in step (3) and stir at a stirring rate of 80 r / min for 2 min to make the microcapsules uniformly dispersed and keep the shell intact.
[0117] (5) Molding and curing: Same as in Example 1. During molding, stainless steel wire mesh electrodes are pre-embedded along the length of the specimen with an electrode spacing of 100 mm, and wires are led out. When the repair is triggered, the DC power supply is turned on to raise the temperature of the crack area to 80~100℃ and maintain it for 30 min to obtain CNT cement-based self-sensing self-healing material, which is denoted as B2.
[0118] Example 3 1. Mixing ratio The difference between this embodiment and Example 1 is the amount of carbon nanotubes used; the rest of the composition is the same as in Example 1. The formulation is shown in Table 3.
[0119]
[0120] 2. Preparation steps: The preparation steps were the same as in Example 1, and CNT cement-based self-sensing and self-healing material was obtained, denoted as B3.
[0121] Comparative Example 1 1. Mixing ratio This comparative example provides a common cement-based material without the addition of carbon nanotubes, polymer-modified phases, or repair units. The formulation is shown in Table 4.
[0122]
[0123] 2. Preparation steps: (1) Dry mixing: Put ordinary silicate cement and standard sand into a mortar mixer and dry mix for 3 minutes at a mixing rate of 140±5r / min until the mixture is uniform.
[0124] (2) Slurry mixing: Add mixing water to the dry material in step (1), stir at a stirring rate of 140±5r / min for 2min, and then stir at a stirring rate of 285±10r / min for 3min until the slurry is homogeneous.
[0125] (3) Molding and curing: Same as in Example 1, ordinary cement-based material was prepared and denoted as D1.
[0126] Comparative Example 2 1. Mixing ratio This comparative example provides a carbon nanotube cement-based material with only self-sensing function, without adding repair units. The formulation is shown in Table 5.
[0127]
[0128] 2. Preparation steps: (1) Preparation of carbon nanotube dispersion: Same as in Example 1.
[0129] (2) Dry material mixing: Same as in Example 1.
[0130] (3) Slurry mixing: Same as in Example 1.
[0131] (4) Molding and curing: Same as in Example 1, carbon nanotube cement-based material with self-sensing function was prepared and denoted as D2.
[0132] Comparative Example 3 1. Mixing ratio This comparative example provides a cement-based material with only self-healing function, without the addition of carbon nanotubes and polymer-modified phases. The formulation is shown in Table 6.
[0133]
[0134] 2. Preparation steps: (1) Dry material mixing: Same as Comparative Example 1.
[0135] (2) Slurry mixing: Add mixing water and silicone defoamer to the dry material in step (1), stir at low speed for 2 minutes, and then stir at high speed for 3 minutes until the slurry is homogeneous.
[0136] (3) Microcapsule introduction: Add two-component type A microcapsules and type B microcapsules to the slurry in step (2) and stir at a stirring rate of 80 r / min for 2 min to make the microcapsules uniformly dispersed and keep the shell intact.
[0137] (4) Molding and curing: Same as in Example 1, a cement-based material with self-healing function is obtained, denoted as D3.
[0138] Comparative Example 4 1. Mixing ratio The difference between this comparative example and Example 1 is that the carbon nanotube doping content is reduced to 0.05 parts, while the remaining composition is the same as in Example 1. The formulation is shown in Table 7.
[0139]
[0140] 2. Preparation steps: The preparation steps were the same as in Example 1, and CNT cement-based self-sensing and self-healing material was obtained, denoted as D4.
[0141] Detection Example 1 Crack detection performance comparison: The crack detection capability was assessed by monitoring the relative resistivity change rate ΔR / R of the cement-based materials prepared in Examples 1-3 and Comparative Examples 1-4 during tensile cracking. The specific method is as follows: A 40mm×40mm×160mm prism specimen was subjected to three-point bending loading. Displacement control was used to induce target cracks of 0.02mm, 0.05mm, 0.10mm, and 0.20mm in diameter, respectively. The width of each target crack was maintained for 30 seconds, and resistance was continuously measured at a sampling frequency of 1Hz. According to ΔR / R=(R W The relative resistance change rate is calculated as (-R0) / R0×100%, where R0 is the initial resistance before cracking, and R... W The resistance at the target crack width; The coefficient of variation of the parallel specimen signal is calculated as CV = σ / μ × 100%, where σ is the standard deviation and μ is the mean.
[0142] For each group, no fewer than three parallel specimens were set up for each target crack width, and the test results are shown in Table 8.
[0143]
[0144] In Table 8, CV is not calculated when there is no identifiable electrical response, indicated by "-".
[0145] When the relative resistance change rate ΔR / R ≥ 5% and the coefficient of variation of the parallel specimen signal CV ≤ 10%, the electrical response under the crack width is determined to be stable and identifiable.
[0146] As shown in Table 8, the cement-based materials prepared in Examples 1 and 2 exhibited relative resistivity changes (ΔR / R) of no less than 5% and signal coefficients of variation (CV) of no more than 10% when the crack width was 0.02–0.10 mm. At a crack width of 0.20 mm, the CVs were 18% and 17%, respectively, indicating decreased electrical response stability. The cement-based material prepared in Example 3 also showed ΔR / R of no less than 5% and CV of no more than 10% when the crack width was 0.02–0.20 mm, demonstrating that increasing the carbon nanotube content can broaden the stable and identifiable crack sensing range. The cement-based materials prepared in Comparative Examples 1 and 3 did not produce identifiable electrical responses. The cement-based material prepared in Comparative Example 2 showed decreased signal stability at a crack width of 0.20 mm. The cement-based material prepared in Comparative Example 4, due to its low carbon nanotube content, did not form a continuous and stable conductive network at any of the tested crack widths.
[0147] Detection Example 2 Crack Repair Effect Comparison After the cracks developed to different widths, the changes in crack width during the curing stage of the cement-based materials prepared in Examples 1-3 and Comparative Examples 1-4 were examined. The specific methods are as follows: A three-point bending displacement control method was used to create target cracks of 0.05 mm, 0.10 mm, 0.12 mm, 0.15 mm, and 0.20 mm in the specimens, respectively. For each group, at least three parallel specimens were prepared at each target crack width. After unloading, the specimens were placed in an environment with a temperature of 20 ± 2℃ and a relative humidity of ≥ 95% for 14 days for repair. At least three measuring points were selected along the crack length to determine the crack width before and after repair.
[0148] Crack repair efficiency (η) W ) by η W =(W0-W 14 The calculation is performed using W0 × 100%, where W0 is the initial crack width before repair, and W... 14To repair the crack width after 14 days; when η W When the crack width is ≥75%, it is determined that the crack width is within the effective self-healing crack window W. h The results are shown in Table 9.
[0149]
[0150] As shown in Table 9, the cement-based materials prepared in Example 1 all achieved repair efficiencies of no less than 75% for crack widths of 0.05–0.15 mm, the cement-based materials prepared in Example 2 all achieved repair efficiencies of no less than 75% for crack widths of 0.05–0.20 mm, and the cement-based materials prepared in Example 3 all achieved repair efficiencies of no less than 75% for crack widths of 0.05–0.12 mm. The cement-based materials prepared in Comparative Examples 1 and 2 achieved repair efficiencies of less than 75% for all tested crack widths; the cement-based materials prepared in Comparative Examples 3 and 4 only achieved effective repair when crack widths were 0.05–0.10 mm, and both achieved a repair efficiency of 67% when crack width was 0.12 mm.
[0151] Detection Example 3 Crack-scale coupling synergy effect verification Based on the comparison results of crack detection performance in Example 1 and crack repair effect in Example 2, the effective crack detection window W for each group of materials was determined. s Self-healing effective crack window W h and its overlapping interval (coupling window) This was to verify the effectiveness and adjustability of the "crack scale coupling" design concept of the present invention.
[0152] Self-sensing effective crack window W s Crack width range is defined as the range of crack widths within which a material can produce a stable and identifiable electrical response, wherein the relative resistance change rate ΔR / R ≥ 5% and the coefficient of variation of the parallel specimen signal CV ≤ 10%.
[0153] Self-healing effective crack window W h Defined as the crack width range within which self-healing units in a material can be effectively triggered and achieve crack filling (repair efficiency ≥ 75%).
[0154] The intersection of self-sensing effective crack windows and self-healing effective crack windows is... Determined; when max(W) s,min W h,min )≤min(W s,max W h,max )hour, If the interval is non-empty, it is determined that the material has effective crack scale coupling. The crack scale windows for each group of materials are shown in Table 10.
[0155]
[0156] As shown in Table 10, the self-sensing effective crack window W of the cement-based materials prepared in Examples 1, 2, and 3 is... s With self-healing effective crack window W h All form a non-empty intersection, and their coupling window The crack widths were 0.05–0.10 mm, 0.05–0.10 mm, and 0.05–0.12 mm, respectively; none of the cement-based materials prepared in Comparative Examples 1–4 formed an effective coupling window. These results indicate that by synergistically controlling the carbon nanotube doping content and the type of self-healing unit, crack sensing and crack repair can be effectively coupled within the same crack width range.
[0157] Detection Example 4 Damage assessment threshold Ω and electrical recovery rate η R Application verification of joint determination To verify that the CNT cement-based self-sensing and self-healing material of the present invention can be used with a damage judgment threshold Ω and an electrical recovery rate η R To assess the feasibility of jointly determining the crack repair status, based on the crack repair test in Example 2, resistance monitoring and crack width measurement were simultaneously conducted on parallel specimens of the CNT cement-based self-sensing and self-healing materials prepared in Examples 1-3. The initial resistance R0 was recorded before cracking; the peak resistance R0 was recorded after loading to the target crack width W0 and holding for 30 seconds. p After 14 days of repair, record the repaired resistance R under the same electrode spacing, test voltage or current, and environmental conditions. a The width W of the crack after repair was measured. 14 .
[0158] According to η R =(R p -R a ) / (R p -R0) calculates the electrical recovery rate; According to η W =(W0-W 14 ) / W0×100% calculates the crack repair efficiency; When the electrical parameter S is expressed as the rate of change of relative resistance, the rate of change of relative resistance after repair is used. a =(R a -R0) / R0×100% is used as the electrical index after repair, and Ω=5%.
[0159] If S a ≤Ω and η R If S ≥ 0.75, the electrical assessment indicates sufficient repair; if S a >Ω or ηR If the value is less than 0.75, the electrical assessment indicates insufficient repair.
[0160] The above electrical judgment results are compared with the geometric criterion η for the same specimen. W ≥75% were compared one by one, and C=N was used as the standard. c The consistency rate is calculated as / N×100%, where N c N represents the number of test pieces for which the electrical and geometric criteria are consistent, and N is the total number of test pieces. The results are shown in Table 11.
[0161]
[0162] As shown in Table 11, the CNT cement-based self-sensing and self-healing materials prepared in Examples 1-3 exhibited a high rate of change in relative resistivity S after repair when the initial crack widths were 0.05 mm and 0.10 mm. a The percentages were 3.55–4.40% and 3.60–4.19%, respectively, both less than the damage assessment threshold Ω (5%); the electrical recovery rate η R The values were 0.78–0.87 and 0.87–0.92 respectively, both higher than 0.75, indicating that the electrical assessment showed sufficient repair. Simultaneously, the crack repair efficiency η of each group of specimens... W The repair rates were 82%–96%, all higher than 75%, and the geometric criterion also showed that all samples were sufficiently repaired. The electrical and geometric criterion results were completely consistent across all 18 specimens, i.e., N = 18. c The value was 18, and the consistency rate C was 100%. Among them, the CNT cement-based self-sensing self-healing material prepared in Example 2 showed η under two crack widths. W The repair rates were 96% and 92% respectively, indicating the best repair effect; as the initial crack width increased from 0.05 mm to 0.10 mm, the η values of each group... W All decreased, while η R All values increased, indicating that the electrical recovery rate has good sensitivity to changes in crack size. These results validate the effectiveness of using a damage assessment threshold Ω and the electrical recovery rate η. R The feasibility of jointly determining the crack repair status can provide a reliable experimental basis for closed-loop judgment of successful or insufficient repair.
[0163] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
[0164] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.
[0165] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.
Claims
1. A CNT-based self-sensing and self-healing material based on crack scale coupling, characterized in that, The CNT cement-based self-sensing and self-healing material includes a cement-based matrix and conductive functional units and self-healing units dispersed in the cement-based matrix; The conductive functional unit is a conductive network formed by carbon nanotubes in the cement-based material, which is used to respond to the generation and propagation of cracks through changes in electrical parameters; The self-healing unit is used to release a repair agent under the action of cracks, so as to achieve crack filling and structural performance restoration; The self-sensing effective crack window W of the CNT cement-based self-sensing and self-healing material s The crack width range within which the conductive functional unit can generate a stable and identifiable electrical response under the action of the crack; The self-healing effective crack window W of the CNT cement-based self-sensing and self-healing material h The self-healing unit is a crack width range that can be triggered under the action of cracks to achieve crack filling, reaction, or structural restoration. The self-sensing effective crack window W s With self-healing effective crack window W h The intersection is ,and .
2. The CNT cement-based self-sensing and self-healing material according to claim 1, characterized in that, The raw materials for the cement-based matrix include silicate cement, standard sand, mixing water, and chemical admixtures; The mass ratio of silicate cement to standard sand is 1:2 to 4, preferably 1:3; The water-cement ratio of the cementitious matrix is 0.4~0.5, preferably 0.45; The standard sand is ISO standard sand conforming to GB / T 17671, with a particle size of 0.08~2.00mm; The chemical admixtures include defoamers and dispersants, and the total dosage of the chemical admixtures is 0.5% to 1% of the mass of silicate cement. The mass ratio of defoamer to dispersant in the chemical admixture is 1:8~12; The defoamer is selected from one or more of silicone defoamers, polyether-modified silicone defoamers, higher alcohol defoamers, and polyether defoamers; The dispersant is selected from one or more of polyvinyl alcohol, polycarboxylic acid dispersants, sodium dodecylbenzenesulfonate, and hydroxypropyl methylcellulose.
3. The CNT cement-based self-sensing and self-healing material according to claim 1, characterized in that, The carbon nanotubes are carboxylated multi-walled carbon nanotubes with an outer diameter of 10-30 nm, a length of 5-30 μm, a purity of ≥95%, a carboxyl mass fraction of 1-3%, and a carbon nanotube content of 0.1-0.2% of the mass of silicate cement. The self-healing unit is selected from one or more of capsule-type repair units, fiber-type repair units, and microtubule-type repair units; Preferably, the self-healing unit is a capsule-type self-healing unit, comprising a core containing repair material and a covering shell; The total dosage of the capsule-shaped repair unit is 0.5-10% of the mass of silicate cement, with an average particle size of 50-500 μm, preferably 100-250 μm; the thickness of the coating shell is 0.5-5 μm, and the coating shell material is selected from one or more of urea-formaldehyde resin, melamine-formaldehyde, polyurea, and polyurethane. More preferably, the capsule-type repair unit is a two-component microcapsule system, including a first microcapsule and a second microcapsule, wherein the core of the first microcapsule is an epoxy resin and / or an epoxy prepolymer, and the core of the second microcapsule is a curing agent and / or a curing accelerator that is matched with the epoxy resin and / or the epoxy prepolymer. The curing agent is selected from one or more of polyamide 650, diethylenetriamine, triethylenetetramine, and modified aliphatic amines; The curing accelerator is selected from one or more of 2,4,6-tris(dimethylaminomethyl)phenol, 2-ethyl-4-methylimidazolium, N,N-dimethylbenzylamine, and substituted urea; The mass ratio of the first microcapsule to the second microcapsule is 1:0.5~1, preferably 1:0.75; And / or, The capsule-type repair unit is a single-component latent microcapsule system, the core of which is a mixture of epoxy resin and / or epoxy prepolymer with latent curing agent and / or latent catalyst; The latent curing agent is selected from one or more of modified imidazole, dicyandiamide, organic hydrazide, and boron trifluoride-amine complex; The latent curing accelerator is selected from one or more of 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2,4,6-tris(dimethylaminomethyl)phenol and substituted urea; The mass ratio of the epoxy resin and / or epoxy prepolymer to the latent curing agent and / or latent catalyst is 1:0.10~0.20, preferably 1:0.15; More preferably, the core of the capsule-shaped self-healing unit further includes a conductive filler, which is one or more of carbon nanotubes, carbon black, and graphene.
4. The CNT cement-based self-sensing and self-healing material according to claim 1, characterized in that, The cement-based matrix also includes a polymer-modified phase, which is a carboxylated styrene-butadiene latex with a solid content of 48-52%. Preferably, the amount of the polymer-modified phase, based on the dry polymer mass, accounts for 2 to 8% of the mass of silicate cement, and more preferably 5%.
5. A method for preparing a CNT cement-based self-sensing and self-healing material as described in any one of claims 1-4, characterized in that, The preparation method includes the following steps: 1) Preparation of carbon nanotube aqueous dispersion: Add carbon nanotubes to part of the mixing water, add dispersant, mechanically stir at a stirring rate of 800~1200r / min for 3~8min, then ultrasonically disperse at a power density of 50~100W / L for 10~60min, let stand for 10min, and take the upper uniform dispersion as carbon nanotube aqueous dispersion. 2) Dry material premixing: Put silicate cement and standard sand into a mixer and dry mix at a mixing rate of 60~150r / min for 1~3min to obtain mixed dry material; 3) Slurry mixing: Add the carbon nanotube aqueous dispersion, polymer modified phase, defoamer and remaining mixing water mentioned in step 1) to the mixed dry material, stir at a stirring rate of 120~180 r / min for 2~4 min, and then stir at a stirring rate of 250~300 r / min for 2~4 min until the slurry is uniform. 4) Introduce self-healing units: Add self-healing units to the slurry that was mixed evenly in step 3), and stir at 60~100 r / min for 1~2 min to disperse the self-healing units evenly and obtain a mixture; 5) Molding and curing: Pour the mixture obtained in step 4) into a mold and perform standard curing until the specified age is reached to obtain the CNT cement-based self-sensing and self-healing material.
6. The preparation method according to claim 5, characterized in that, In step 1), the dispersant is selected from one or more of polyvinyl alcohol, polycarboxylic acid dispersants, sodium dodecylbenzenesulfonate, and hydroxypropyl methylcellulose; The mass ratio of the carbon nanotubes, dispersant, and a portion of the mixing water is 1:(2.5~5):(100~200).
7. The preparation method according to claim 5, characterized in that, In step 5), the standard curing conditions include: ambient temperature of 18~22℃, relative humidity ≥95%, curing age ≥28d; after pouring, the formwork is removed after standing for 20~24h, and after removal, the formwork is placed in the standard curing environment for curing until the specified age.
8. The preparation method according to claim 5, characterized in that, The preparation method also includes pre-embedding electrodes during the molding process of the CNT cement-based self-sensing and self-healing material; The electrodes are used to apply voltage or current to the CNT cement-based self-sensing and self-healing material, causing the conductive network to generate Joule heating.
9. The application of the CNT cement-based self-sensing and self-healing material as described in any one of claims 1-4 in the health monitoring and crack self-repair of structures in super high-rise buildings, rail transit, or underground engineering.
10. A method for coordinating crack self-sensing and self-repairing using the CNT cement-based self-sensing and self-repairing material according to any one of claims 1-4, characterized in that, The method includes the following steps: S1. Initial state and real-time monitoring: The CNT cement-based self-sensing and self-healing material in good service condition conducts real-time electrical monitoring through its internal conductive functional unit, continuously collects electrical index S, and dynamically senses the generation and expansion state of cracks. S2. Damage signal discrimination: When the real-time acquired electrical index S enters the electrical threshold window When, and the signal duration is ≥ t n If the condition is not met, proceed to the coupling window determination stage; if the determination condition is not met, return to step S1 to maintain the real-time monitoring state. S3. Entering Critical State and Repair Trigger: Determine whether the crack width W corresponding to the current electrical index S falls within the crack scale coupling window. Confirm entry into the crack-scale coupling window. Then, the corresponding repair mechanism is triggered: When a two-component microcapsule self-healing unit is used, a passive triggering mode is adopted, which relies on the stress of crack propagation to rupture the microcapsule shell, and the two-component repair agent is released into the crack space simultaneously. When using a single-component latent microcapsule self-healing unit, an active triggering mode is adopted. By applying voltage or current to the built-in electrodes of the CNT cement-based self-sensing self-healing material, the Joule heating effect of the conductive functional unit is used to raise the temperature of the crack area to a preset temperature range, thereby activating the latent curing component to start and accelerate the repair reaction. S4. Crack filling and conductive network reconstruction: The repair agent flows into the crack space and solidifies, filling the crack defects and bridging the crack interface; at the same time, the conductive path in the repaired area is gradually reconstructed, and the electrical index S of the CNT cement-based self-sensing self-healing material gradually decreases with the repair process. S5. Closed-loop verification of repair effect: After the repair is completed, obtain the electrical index S after repair. a And calculate the electrical recovery rate η R ; If the electrical index S is repaired a ≤Damage threshold Ω, and electrical recovery rate η R If the value is ≥0.75, the repair is considered successful. The CNT cement-based self-sensing and self-healing material is restored to a state where it can continue to be used. Return to step S1 to enter the next monitoring cycle. If the electrical index S is repaired a >Damage assessment threshold Ω, or electrical recovery rate η R If the value is less than 0.75, the repair is deemed insufficient, triggering a secondary repair process or issuing a damage alarm. Preferably, in step S1, the electrical index S is the relative resistance change rate ΔR / R or the impedance change. Preferably, the electrical response of the CNT cement-based self-sensing self-healing material is tested in advance under different crack widths to establish the correspondence between the electrical index S and the crack width W, and to determine the coupling window with crack scale. Corresponding electrical threshold window Simultaneously, a damage assessment threshold Ω and a minimum duration assessment time t are set. n ; Preferably, when the electrical index S is the relative resistance change rate ΔR / R, Ω is 5%; when the electrical index S is the impedance change, Ω is the impedance change corresponding to the smallest identifiable crack. Preferably, in step S2, the shortest duration determination time t n For 10~60s; Preferably, in step S5, the electrical recovery rate η R Satisfying η R =(R p -R a ) / (R p- R0), where R0 is the initial resistance, R p R is the peak resistance at the crack. a The resistance after repair; If η R =1 indicates that the resistance has completely returned to its initial state, if η R =0 indicates that the resistance did not decrease at all after the repair, and there was no repair effect whatsoever; if 1≥η R A value ≥0.75 indicates a good repair effect; if 0 < η R A value <0.75 indicates insufficient repair effect; Preferably, in step S5, the repaired electrical index S a This refers to the rate of change of relative resistance or the amount of change of impedance after repair.